Perlindungan terhadap inventor terkait unsur kebaruan paten yang hapus akibat tidak membayar biaya tahunan - Moza Ramadhani; Muhamad Amirulloh; Pupung Faisal (University of Merdeka Malang, 2021)
The elimination of a registered patent causes the inventor's exclusive right to use his invention to be lost, it causes losses to the inventor as a result of not being able to reuse the invention. In addition, the inventor also loses economic rights to the patent because he cannot use his invention. The regulation regarding the abolition of patents stipulated in Article 130 letter d of the Patent Law is deemed not to provide adequate protection for inventors. Based on this, the aim of this research is to determine the legal qualifications of the Patents Directorate's actions in consuming registered patents and to determine the legal actions that should be taken by inventors to get their patents back. In research, the method used is normative juridical, and descriptive-analytical research specifications. The aim is to analyze the prevailing laws and regulations and legal theory with practical implementation in reality. Data were collected through literature and field studies, then analyzed using qualitative normative methods. The final result of the research states that the elimination of patents is due to not paying annual fees and making the patent into the public domain as in Article 130 letter d of the Patent Law is against the Alter Ego Principle because the elimination of the patent makes the patent turn into the public domain and shows that the patent has lost its novelty element.How to cite item: Ramadhani, M., Amirulloh, M., Faisal, P. (2021). Perlindungan terhadap inventor terkait unsur kebaruan paten yang hapus akibat tidak membayar biaya tahunan. Jurnal Cakrawala Hukum, 12(1).51-59. doi:10.26905/idjch.v12i1.4717.